Achieving Exceptional High Ductility in Binary Mg–6Zn Alloy Wire by Grain Boundary Strengthening and Twinning‐Induced Plasticity. Issue 5 (15th February 2021) - Yan, Kai; Cheng, Honghui; Liu, Yi; Liu, Huan; Fang, Shuangquan; Bai, Jing
Abstract : Mg–6Zn alloy wires are prepared by the combination of hot direction extrusion and multi‐pass hot drawing. The tensile results show that this technology achieves an exceptional tensile elongation of about 18%, as well as the yield strength of 175 MPa and the ultimate tensile strength of 310 MPa when the drawing temperature is 350 °C. Meanwhile, it also exhibits the highest strain‐hardening data compared with the other wire samples. The microstructure characterizations show that the near single‐phase α‐Mg microstructure with the MgZn2 nanoprecipitates on grain boundaries and it can significantly produce twin intersections and stacking faults under cold bending deformation. The exceptional high elongation can be attributed to the grain boundary strengthening of nanoprecipitates and twinning‐induced plasticity. Abstract : A tensile elongation of about 18% is achieved in Mg–6Zn alloy wire with a near single‐phase microstructure through a series of suitably hot forming techniques. The exceptional tensile elongation can be attributed to its higher work hardening caused by the grain boundary strengthening of nanoprecipitates and twins and stacking faults induced by cold deformation.